Two-Layer Optimization Method of Web of Cells Network Considering Source-Load Flexibility Resources - Huang, Jinhua; Song, Xudong; Tang, Jiandong; Jin, Ke; Liu, Dong; Weng, Jiaming (China International Conference on Electricity Distribution, 2024)
The uncertainty and volatility caused by the current high proportion of distributed generation access have brought new challenges to the economy and security of distribution network. Therefore, a Two-layer optimization method of web of cells network is proposed, which considers the uncertainty of source and load. Firstly, the flexibility of various source-load in the distribution network are considered, and the flexibility evaluation index is established from the flexibility supply and demand balance and branch channel adequacy. Secondly, a Two-layer optimization model of distribution network considering economy and flexibility is established. The upper model takes the grid division strategy of distribution network as the decision-making subject, and the lower model takes the flexibility of supply and demand side to adjust the output of resources as the decision-making subject. Finally, the simulation results verify the rationality and effectiveness of the proposed optimization method.